Description of Blood Pressure in Tuak Consumers in Porsea District - Elisa Vebiola Lasmarisi Marpaung; David MT Simangunsong (Jurnal EduHealth, 2023)
Hypertension is a disease that has become a big problem in the world. Based on WHO's data in 2018, this hypertension affects about 22% of the world's population, and about 25.8% of the Indonesian population aged 18 years. One of the risk factors for hypertension was consuming alcohol. Palm wine is a traditional drink that contains alcohol. The purpose of this study was to determine the description of blood pressure, frequency and quantity of palm wine consumption in adult men in Porsea District. This study used a descriptive method with a cross-sectional approach. Using 98 adult males as a sample. Blood pressure examination wascarried out in accordance with the provisions of JNC VIII using a stethoscope and aphygmomanometer. Provisions of the quantity and frequency of palm wine consumption were measured using a questionnaire. With 100 adult males as subjects which is consuming palm wine in Porsea District, based on the quantity of palm wine consumption, the distribution with the most was level 3 drinkers (63.0%). Based on the frequency of palm wine consumption, the distribution with the most is frequent drinkers (80.0%). Based on blood pressure, the highest distribution was those with grade I hypertension (40.0%). Most of the research subjects belonged to the group of level 3 drinkers, frequent drinkers, and most experienced level I hypertension. So based on this data, palm wine can indirectly affect the increase pf blood pressure in adult males in Porsea District.